VERTICAL PARKING DESIGN BASED ON ANALYSIS OF ON STREET PARKING AND ITS IMPACT ON TRAFFIC PERFORMANCE IN JENDERAL SUDIRMAN ROAD, BANDUNG CITY - Syahril, Muslina
The condition of on street parking on Jalan Jenderal Sudirman Bandung between Otista and Gardujati intersection which has 51 SRP for motorbikes and 86 SRP for light vehicles often causes congestion in this shopping areas and reduces road performance. To overcome this problem, it is necessary to increase the availability of parking which is able to replace on street parking in the form of vertical parking on vacant land around the road. The purpose of this Final Project report is to design a vertical parking layout as needed with the maximum accumulation method. The data used are primary data and secondary data. Primary data was obtained from the results of a survey for 1 working day, Monday 20 March 2022. Meanwhile, secondary data was obtained from related agencies. Analysis was carried out on parking characteristics and road performance parameters. As the basis for the analysis, Pedoman Perencanaan dan Pengoperasian Fasilitas Parkir 1998 and MKJI in 1997 were used. From the results of the survey data processing it is known that the characteristics of on street parking at the study site are the highest parking duration of 15 minutes, the highest accumulation and parking volume at 11.00 - 11.15 WIB for motorbikes and 12.45-13.00 for lights vehicles, the highest parking index was at 12.45-13.00 and the highest PTO was 2.67 for light vehicles. This has a negative impact on the performance of road, road capacity reduced by 44.4%, the degree of saturation during rush hours at 17.00-18.00 WIB by 0.49 increased to 0.87, the level of service category A became D, and the speed of light vehicles became 11.14 km/h. The number of parking needs that will be served by vertical parking for up to 15 years of the plan is 116 SRP for cars and 240 SRP for motorbikes. The vertical parking layout is designed in the form of a 2-storey building on vacant land that widens at an angle of 90° and circular ramps, as well as a 4-level Puzzle Parking System without widening the land. Based on the value of NPV, BCR, and payback period, parking building and automatic parking projects are not economically feasible for up to 15 years of the plan. But the automatic parking building is more recommended than parking based on the value of financial analysis.